The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1516-89132003000200022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvest period on the quality of storage roots and protein content of the leaves in five cassava cultivars (Manihot esculenta, Crantz)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…In fact, gari produced from cassava harvested in the rainy season (15MAP) showed a reduction in starch content because of its mobilization for new shoot formation in the new growth cycle. This is in agreement with what was reported by Filho [ 57 ], Madore [ 58 ], Sriroth et al [ 59 ], Sagrilo et al [ 60 ], and Nuwamanya et al [ 49 ]. Furthermore, cassava roots starch may decrease progressively as plant aged after optimal starch storage ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, gari produced from cassava harvested in the rainy season (15MAP) showed a reduction in starch content because of its mobilization for new shoot formation in the new growth cycle. This is in agreement with what was reported by Filho [ 57 ], Madore [ 58 ], Sriroth et al [ 59 ], Sagrilo et al [ 60 ], and Nuwamanya et al [ 49 ]. Furthermore, cassava roots starch may decrease progressively as plant aged after optimal starch storage ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…This might be due to varietal differences and harvest season as carbohydrate is highly concentrated during dry season compared to the rainy season. The reduction of carbohydrate for the gari samples obtained at 15 months was probably due to the rain which facilitates the hydrolysis of carbohydrate to sugar for shoots regrowth after prolonged water stress [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sagrilo et al (2002) assessed the performance of cassava cultivars in the Northwest Paraná at different harvest times and concluded that, for those conditions, the physiological rest period at the end of the second crop cycle was more indicated for harvest, due to the higher production of the storage root fresh and dry matter and starch. Sagrilo et al (2003) observed that the cultivars IAC 13, IAC 14 and Fécula Branca had high dry matter content in the storage roots. They also emphasized the importance of selecting the genotypes which had high dry matter content in the storage roots, to obtain better yield.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, assessments were carried out in a total of eight different environments. The soils of both the locations have been classified as distrophic Red latosoil (Embrapa, 1999;Sagrilo et al, 2003). The climate of Maringá is Cw´h type, (according to Köppen' classification), with a mean annual temperature of 22.4°C and mean annual rainfall of 1,639 mm, while that of Araruna is Cfb type, with a mean annual temperature of 21.5°C…”
Section: Methodsmentioning
confidence: 99%